2011
DOI: 10.1029/2010jc006884
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Coupled Ocean-Atmosphere Response Experiment flux algorithm with CO2, dimethyl sulfide, and O3

Abstract: [1] Updates for the Coupled Ocean-Atmosphere Response Experiment (COARE) physically based meteorological and gas transfer bulk flux algorithms are examined. The current versions are summarized and a generalization of the gas transfer codes to 79 gases is described. The current meteorological version COARE3.0 was compared with a collection of 26,700 covariance observations of drag and heat transfer coefficients (compiled from three independent research groups). The algorithm agreed on average to within 5% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
140
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(145 citation statements)
references
References 59 publications
(100 reference statements)
5
140
0
Order By: Relevance
“…Bubble-mediated gas transfer has been studied in the laboratory (Asher et al, 1996;Rhee et al, 2007) and using models (e.g. Woolf, 2005;Woolf et al, 2007;Fairall et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bubble-mediated gas transfer has been studied in the laboratory (Asher et al, 1996;Rhee et al, 2007) and using models (e.g. Woolf, 2005;Woolf et al, 2007;Fairall et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al, 2011;Goddijn-Murphy et al, 2012;Bell et al, 2015). It has been suggested that the difference between the open-ocean gas transfer velocities of CO 2 and DMS is due to the reduced importance of bubble-mediated exchange for DMS (Blomquist et al, 2006;Fairall et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Details of the original development of the COARE algorithm for meteorological fluxes (sensible heat, latent heat, momentum) can be found in Fairall et al (1996Fairall et al ( , 2000, and the subsequent development of the algorithm to include gas transfer is shown in Hare et al (2004) and Fairall et al (2011). Advancements in sensor technologies led to the application of the micrometeorological direct covariance method to estimate air-sea fluxes at hourly time scales on the atmospheric side of the interface.…”
Section: Noaa-coarementioning
confidence: 99%
“…The latest version of the code (COAREG3.1) includes a scheme to partition the wind stress into tangential and wave-induced components (see Fairall et al (2011) for more details).…”
Section: Noaa-coarementioning
confidence: 99%
“…[10] Large databases, such as SOCAT (CO 2 ), MEMENTO (nitrous oxide (N 2 O) and methane), [11] and GSS (dimethyl sulfide, DMS) have supported the development of global climatologies, [12] reassessment of regional and global ocean sinks and sources [13,14] and development of prognostic models. [15] Studies of physical processes have produced new parameterisations and algorithms [16][17][18][19] and remote sensing approaches [20] for quantifying air-sea exchange. Observational frameworks and predictive models have increased in coverage, complexity and robustness, [21][22][23] which is critical for establishing mitigation and adaptation responses to climate change.…”
Section: Introductionmentioning
confidence: 99%